Pengaruh Tawas dan Waktu Pengadukan Terhadap Kadar Fosfat pada Limbah Cair Laundry di Martapura Kabupaten Banjar - Rifani Alfian; Sulaiman Hamzani; Abdul Khair (JURNAL KESEHATAN LINGKUNGAN: Jurnal dan Aplikasi Teknik Kesehatan Lingkungan, 2017)
Abstract: Effect of Stirring Time Alum And Phosphate Levels In Liquid Waste Martapura Laundry In Central District. One of the wastes produced is phosphate. Disposal of waste which contains phosphates in the water can cause eutrophication processes in the aquatic environment. Therefore it needs proper methods for treating waste that contains a lot of laundry phosphate compounds that safely discharged into the environment. This study aims to determine the effect of the use of alum and alum stirring time on levels of phosphate in laundry wastewater XXX in Martapura, Banjar.This type of research is shaped Experimental research. Design The study design is randomized pretest-posttest control group design. The sample was liquid waste from the laundry XXX Laundry washing process that represents the entire population of data analysis using One Way ANOVA Test. The result of a decrease in the average levels of phosphate in sequence on each variation of stirring time, ie 92.7%; 99.6%; and 96.7%. The statistical test used is One Way Anova test. Based on an analysis using One Way ANOVA in the treatment group p-value (0.00